Occupational downgrading, job tasks, and the return intentions of the Ukrainian refugees in Poland - Piotr Lewandowski (EconPol Forum, 2025)
Ukrainian refugees in Poland have a high employment rate (55-65 percent), but most work in low-skilled jobs, with around 40 percent feeling overskilled compared to their qualifications. Refugees face a marked increase in routine task intensity (RTI) in Poland, performing more repetitive, less skill-intensive work than in Ukraine ("task degradation"). This is particularly true for those with tertiary education or poor Polish language skills. Task degradation has influenced many refugees to reconsider staying in Poland. By 2023, 20 percent of refugees who initially planned to stay in 2022 expressed intentions to return to Ukraine - the stronger the task degradation, the more likely this change in plans. Poland's limited integration policies and weak support for skill alignment have hindered refugees' ability to secure jobs matching their qualifications. This poses longterm risks for both refugees and Poland's labor market. Addressing skill mismatches, improving language training, and providing pathways to skilled jobs could enhance refugees' contributions to Poland and prepare them for meaningful roles upon returning to Ukraine.
Keywords: 330